O-GlcNAcylation in ischemic diseases - Shi, Rui-Rui; He, Tian-Qi; Lin, Meng-Si; Xu, Jian; Gu, Jin-Hua; Xu, Hui (Frontiers in Pharmacology, 2024)
Protein glycosylation is an extensively studied field, with the most studied forms being oxygen or nitrogen-linked N-acetylglucosamine (O-GlcNAc or N-GlcNAc) glycosylation. Particular residues on proteins are targeted by O-GlcNAcylation, which is among the most intricate post-translational modifications. Significantly contributing to an organism's proteome, it influences numerous factors affecting protein stability, function, and subcellular localization. It also modifies the cellular function of target proteins that have crucial responsibilities in controlling pathways related to the central nervous system, cardiovascular homeostasis, and other organ functions. Under conditions of acute stress, changes in the levels of O-GlcNAcylation of these proteins may have a defensive function. Nevertheless, deviant O-GlcNAcylation nullifies this safeguard and stimulates the advancement of several ailments, the prognosis of which relies on the cellular milieu. Hence, this review provides a concise overview of the function and comprehension of O-GlcNAcylation in ischemia diseases, aiming to facilitate the discovery of new therapeutic targets for efficient treatment, particularly in patients with diabetes.